Surface evolution of Al–Si–Cu alloy in a high frequent pulsing oxyacetylene combustion. (March 2022) - Liu, Lei; Tang, Chengwei; Li, Boyan; Li, Jianping; Bao, Tong; Yang, Zhong; Guo, Yongchun; Feng, Wei; Lei, Zhuo; Li, Haiying
Abstract: To understand the surface evolution in unsteady thermal environment of diesel engine, piston Al–Si–Cu alloy was ablated by a high frequent pulsing carburizing oxyacetylene combustion. The tested samples displayed good correlation with the characteristics of some bench tested pistons. As the loading cycles increased, the roughness slightly declined first and then rose sharply. Hardness evolution, micro-morphology, element and phase analysis suggested the surface roughness was mainly controlled by the thermal stress induced defects. And in combination with thermodynamics, the source of Al in surface deposited rimous carbon was ascertained to be chemical reactions between carburizing combustion and the Al–Si–Cu alloy.